The study of forest dynamics in the pergumid climate of Western Sayan mountains (Ermakovsky research station of V. N. Sukachev Institute of Forest, Russian Academy of Sciences, Siberian Branch) - D. I. Nazimova; M. E. Konovalova; D. M. Danilina; E. I. Ponomarev; N. Yu. Stashkevich; S. D. Baboy (Сибирский лесной журнал, 2015)
The Ermakovsky territory research station (53°17´–52°28´ N, 92°49´–93°20´ E) has served as a long-term site for studies of mountain forest ecosystem structure and its dynamics during the last 50 years. The most interesting results of study in 2000–2014 are presented in the paper concerning biodiversity and forest succession in primary and secondary forest types forming the chern forest formation with Siberian pine (Pinus sibirica Du Tour) and Siberian fir (Abies sibirica L.). The data of remote sensing confirm differentiation of landscapes into altitudinal belt complexes (ABC) that are characteristic for windward macroslopes of the West and East Sayans: Scotch pine-Birch-Aspen subtaiga (Pinus sylvestris L., Betula pendula Roth., Populus tremula L.), chern forest with (Pinus sibirica and Abies sibirica), mountain Siberian fir (Abies sibirica) taiga within perhumid climate, subalpine open woodlands with (Pinus sibirica and Abies sibirica). They were singled out earlier with traditional methods. Position of the mountain polygon-transect (study area) in the system of natural zonation of Altai-Sayan ecoregion and its belonging to barrier-rain mountain landscapes of South Siberia are defined more exactly with help of forest inventory and remote sensing data. Initial phases of forest successions by the above mentioned four ABCs are considered with special attention to regeneration of Pinus sibirica. In contrast to Abies sibirica it remains weak or absent for more than 50 years. It shows unstable positions of Siberian pine in all ABCs due to high general humidity and well developed herb layers. For chern ABC, the dynamics of primary and secondary stands structure are researched on a number of representative plots with the use of tree layer, shrub layer and herb layer 1:100 mapping three times in a 45 year period. It is shown that species number and composition remain stable on permanent plots whereas synuzial diversity and the share of their participation in herb layer vary significantly and influence location of regeneration. The features of coniferous ecosystems with Pinus sibirica and Abies sibirica referred to chern forests correspond to the status of preserved objects due to their unique and virgin character. A number of Pinus sibirica genetic reserves (permanent plots) are located in the chern ABC.